Improving high-temperature performance of lithium-rich cathode by roll-to-roll atomic layer deposition of titania nanocoating for lithium-ion batteries. (1st December 2021) - Panda, Ananya; Patra, Jagabandhu; Hsieh, Chien-Te; Huang, Yang-Chih; Gandomi, Yasser Ashraf; Fu, Chun-Chieh; Lin, Ming-Hsien; Juang, Ruey-Shin; Chang, Jeng-Kuei
Highlights: Spatial atomic layer deposition was used to coat TiO2 layers on Li-rich cathode. TiO2 -coated Li-rich cathodes are cycled within 2.0–4.8 V at 60 °C for 200 cycles. High-temperature rate capability and cyclic stability are strongly improved. TiO2 layer is capable of effectively alleviating metal migration and cation mixing. The technique provides a continuous coating on Li-rich cathodes with > 1.2 m min −1 . Abstract: Lithium-rich layered oxides are attractive cathode materials for next-generation lithium-ion batteries thanks to their ultra-high specific capacities commonly surpassing 200 mAh g − 1 . However, poor cycling stability and sluggish reaction kinetics inhibit their widespread applications. To alleviate this critical drawback, in this work, we have developed a unique roll-to-roll atomic layer deposition (R2R ALD) apparatus to continuously coat TiO2 nanolayers on the Li-rich cathode sheets. To confirm the efficacy of the design, the TiO2 -coated Li-rich cathodes were electrochemically cycled within an aggressive voltage range (2.0–4.8 V) at 25 and 60 °C for 200 cycles. The rate capability, cyclic stability, and electrode polarization were significantly improved for high-temperature operation via coating a finely tuned TiO2 nanolayer on the layered cathodes. The TiO2 nanolayer effectively alleviates the metal migration and cation mixing within the Li-rich layered structure during high-temperature cycling. The R2R ALD technique engineered in this study enables continuous coating of TiO2 nanolayers on the Li-rich electrodes with ultra-high production rates (> 1.2 m min −1 ). Graphical abstract: Image, graphical abstract